2012
DOI: 10.3993/jfbi12201203
|View full text |Cite
|
Sign up to set email alerts
|

Research on Heel Height of Women's Shoes Based on Walking Analysis

Abstract: The purpose of this study is to investigate how the different heel heights of women's shoes influence walking according to walking analysis findings. Identifying heel heights that do not impair walking comfort were also investigated. Ten female university students were chosen as subjects and asked to wear sample pumps with heel heights of 1.5, 3.5, 5.5, and 8.5 cm. The walking experiments focused on walking movements, muscular activities of the lower limbs, and ground reaction at the point of impact. A questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The increased activity of the peroneal muscles could be due to the control of the increased plantarflexion when standing in high heels. Another response to the increased activity of the peroneal muscles is related to its role of protection of the foot from sudden inversion (supination increase) about the ankle and a stabilizer [19,44]. In both Srivastava et al's study and Henderson and Piazza's study it was declared that muscles of GC L and GC M responded differently to use of HHS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increased activity of the peroneal muscles could be due to the control of the increased plantarflexion when standing in high heels. Another response to the increased activity of the peroneal muscles is related to its role of protection of the foot from sudden inversion (supination increase) about the ankle and a stabilizer [19,44]. In both Srivastava et al's study and Henderson and Piazza's study it was declared that muscles of GC L and GC M responded differently to use of HHS.…”
Section: Discussionmentioning
confidence: 99%
“…Do Nascimento et al reported that the gastrocnemius muscle participated for a longer period during the gait cycle when wearing 7 cm stiletto heels than when walking barefoot [7]. Hosoya et al reported that there was a significant difference and positive correlation in gastrocnemius muscle activity especially in 8.5 cm heel height [19]. Additionally, a study carried out with 10 professional female dancers (more than five years' dancing history, and wearing four types of shoes with a heel height of 1.0 cm, 4.5 cm, 7.5 cm and 10 cm, designated as flat, low heel, medium high heel and high heel shoe, respectively) with mean age 22.8 years using EMG showed that there were significant increases in GC M , GC L , TA and soleus muscles in heightened heel shoes compared to dancers wearing flat heels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, walking with high heeled shoe have required both more efforts and many impact like on the balance, posture, gait kinematics and foot stability of the wearer 9 . On the other hand, this type shoes cause muscle fatique, repetitive strain injuries, low back disorder and muscle imbalance 22 . Subject's stride length is reduced and in order to keep a normal speed, the subject has to increase the frequency of her pace to meet demanding both in cardiovascular stres and oxygen consumption 30 .…”
Section: Negative Effects Of High Heeled Shoesmentioning
confidence: 99%
“…For example, they are dressed because of having more attractive appearance 20 . Moreover, most of females like HHS because they have thought that these shoes provide a sense of self esteem, attractiveness and psychological well being 19,21 and give to female sense of longer and slim legs 17,22 . Wearing of HHS is more common in between young females 22 .…”
Section: Reasons For Using By Femalesmentioning
confidence: 99%